EFEKTIVITAS DAUN SPEARMINT (Mentha spicata) SEBAGAI REPELLENT LALAT RUMAH (Musca domestica) - Sambuaga, Joy V.I.; Ngolo, Sintia D.; Pandeana, Marlyn M.; Robert, Daniel; Maramis, Jeana L. (Jurnal Kesehatan Lingkungan, 2022)
The house fly (Musca domestica) is a mechanical vector that has perfect morphology. The use of repellents generally does not directly kill insects but functions as a repellent against the presence of insects. Mint leaves (Mentha spicata) contain volatile oil compounds and chemicals including myrcene, L-Limonene, Cis-Dhydrocarvone and L-Carvone. The purpose of this study was to determine the effectiveness of spearmint leaves (Mentha spicata) as a house fly repellent (Musca domestica). This type of research is Quasi Experiment which consists of 3 experimental groups and 1 control group. This research was conducted at the Entomology and Parasitology Laboratory, Department of Environmental Health, Health Polytechnic, Manado Health Department. The sample used in the study was 200 individuals, data analysis using the One Way Anova test. The independent variable in this study was spearmint leaf (Mentha spicata) and the dependent variable was the house fly (Musca domestica). The results obtained from observations for 26 minutes were the number of flies that arrived at the control was 41, at 1 gram 1 tail, at 2 gram 34 and at 3 gram 34. Based on the results of the One Way Anova test, p value = 0.010 0, 05 which means Ho is rejected and there is no significant difference between 1 gram, 2 gram and 3 gram controls. The treatment dose that reached the standard of repellant protection was 1 gram with a protective power of 98%, further research is needed using the spearmint leaf extract method.